THE SIGNIFICANCE OF ISLAMIC VALUES AND ENLIGHTENMENT IN THE CONTEMPORARYERA (Eureka Journal of Humanities and Social Research, 2026)
The article explores how Islamic values and enlightenment beliefs impact contemporary society through their effects on educational systems and cultural identity formation. The study demonstrates that Islamic enlightenment traditions provide essential frameworks for ethical conduct, social cohesion, and intellectual development in secular modern societies. The findings indicate that Islamic enlightenment principles offer valuable perspectives for resolving conflicts between tradition and modernity, promoting intercultural dialogue, and fostering holistic human development in globalized contexts.
Keywords: Enlightenment, contemporary society, cultural identity, moral education, spiritual development, social ethics, religious knowledge, modernization